Comparative Investigation of 0.5Li2MnO3·0.5LiNi0.5Co0.2Mn0.3O2 Cathode Materials Synthesized by Using Different Lithium Sources - Wang, Peng-Bo; Luo, Ming-Zeng; Zheng, Jun-Chao; He, Zhen-Jiang; Tong, Hui; Yu, Wan-jing (Frontiers in Chemistry, 2018)
Lithium-rich Manganese-based cathode materials has been attracted enormous interest as one of the most promising candidates of cathode materials for next-generation lithium ion batteries because of its high theoretic capacity and low cost. In this study, 0.5Li2MnO3·0.5LiNi0.5Co0.2Mn0.3O2 materials are synthesized through a solid-state reaction by using different lithium sources, the synthesis process and the reaction mechanism are investigated in detail. The morphology, structure and electrochemical performances of the material synthesized by using LiOH·H2O, Li2CO3 and CH3COOLi·2H2O have been analyzed by using Thermo gravimetric analysis (TGA), X-ray diffraction (XRD), Scanning electron microscope (SEM), Transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS) and electrochemical measurements. The 0.5Li2MnO3·0.5LiNi0.5Co0.2Mn0.3O2 material prepared by using LiOH·H2O displays uniform morphology with nano particle and stable layer structure so that it suppresses the first cycle irreversible reaction and structure transfer, and it delivers the best electrochemical performance. The results indicate that LiOH·H2O is the best choice for the synthesis of the 0.5Li2MnO3·0.5LiNi0.5Co0.2Mn0.3O2 material.